Development of Functional Food Project Learning Tools for Food Chemistry Course - Kurnia, Nova; Liliasari, Liliasari; Adawiyah, Dede Robiatul; Supriyanti, Florentina Maria Titin (JTK (Jurnal Tadris Kimiya), 2021)
This study aims to develop functional food project learning tools for the food chemistry course. This project learning tools consist of an implementation guide accompanied by a project appraisal rubric. The development of learning tools was based on the Dick and Carey model with three stages: needs analysis, development, and validation. The needs analysis shows an increase in non-communicable diseases in Indonesia and the world. Functional food has not been taught in food chemistry courses and the abundance of local food in Lombok Island with its various functional potency. The development stage involves designing project instructions accompanied by an assessment rubric. Two experts in food chemistry carried out the validation stage of the project learning tools. The instrument used was a questionnaire related to the suitability of the project objectives with the learning outcomes of food chemistry, the clarity of project-based learning syntax, the relevance of project topics to Lombok food, aspects of the language used, and an assessment rubric. The results show that all validated aspects are accepted with a few notes which have been further improved. Thus, the project learning tools can be used for functional food projects in food chemistry courses.